Partisipasi Elekronik: Pemanfaatan Monggo Lapor dalam Aplikasi Magelang Cerdas di Kota Magelang - Apri Rizkya Dwi Anggita; Ismi Dwi Astuti Nurhaeni (Jurnal Mahasiswa Wacana Publik, 2021)
Concept of e-participation in smart city refers to the participation of citizens and other parties by utilizing information and communication technology (ICT). The use of ICT is carried out by the Magelang City Government with the creation of the Magelang Cerdas application. Magelang Cerdas is an android based application by developing a one stop public service portal which consists of several features, one of which is Monggo Lapor. The purpose of this research is to analyze the degree of community involvement in the City of Magelang through the use of Monggo Lapor in the Magelang Cerdas Application with the Macintosh theory (2004) which divides the degree of e-participation into three: e-enabling, e-enganging, and e-empowering and identifying factors which forms e-participation in the context of Smart City with the theory of Nam & Pardo (2011). This research use descriptive qualitative approach. Methods of data collection through interviews and documentation. The data obtained were processed by interactive analysis. The results show that the level of the degree of e-participation utilizing the Monggo Lapor Magelang Cerdas application is at the e-enganging level. E-participation of Magelang City in the context of Smart City is influenced by adequate technology, institutions that apply transparency and human capacity in terms of qualified ASN. However, human capacity in terms of community skills is considered to be lacking because the use of the Magelang Cerdas application has not been fully utilized by residents.